2023
DOI: 10.9734/jcti/2023/v13i3-4243
|View full text |Cite
|
Sign up to set email alerts
|

Management of Nodular Nasal Basal Cell Carcinoma with Wide Excision, Transpositional Median Forehead Flap, Forehead Split Thickness Skin Graft: Case Report

Joko Wibowo Sentoso,
Henky Agung Nugroho,
Affandi Wiramur

Abstract: Introduction: Basal cell carcinoma (BCC) is the most common skin type cancer with an incidence rate of around 75-80%. The most common location is in the head and neck area around 70-80% and followed by other body parts around 25% consist of the penis, vulva or perianal area and 5% on the skin. BCC occurs more frequently in light-skinned individuals compared to dark-skinned individuals. The incidence rate is relatively lower in Asians, blacks ethnic, and Hispanics. Case Presentation: A 66 years-old woman … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…In subsequent follow up at second month only 4.8% of cases in group-A had bradycardia and no patients had bradycardia after that. Alsmman and Mounir, [4] found that there were no recorded cases of hypotension, bradycardia, or hypoglycemia during the course of oral propranolol treatment [38,39].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In subsequent follow up at second month only 4.8% of cases in group-A had bradycardia and no patients had bradycardia after that. Alsmman and Mounir, [4] found that there were no recorded cases of hypotension, bradycardia, or hypoglycemia during the course of oral propranolol treatment [38,39].…”
Section: Discussionmentioning
confidence: 99%
“…There is often continued gradual regression of the color and bulk of the tumor until 10 to 12 years of age" [3]. "The proliferation and involution phases of the tumor are controlled by multiple regulators that include molecular, cellular and hormonal changes" [4,38,39]. "However, spontaneous regression is no guarantee of a satisfactory cosmetic result" [5].…”
Section: Introductionmentioning
confidence: 99%